Biochemical indicators of inflammation and dysbiosis in the oral cavity of patients with mandibular fractures on the background of the hepato-biliary pathology - Sergey Polishchuk; Anatoliy Levitsky (Kazimierz Wielki University, 2018)
Purpose: To determine the effect of hepatobiliary pathology (HBP) on the development of dysbiosis and inflammation in the oral cavity of patients with fractures of the lower jaw (mandible). Methods: 157 patients with HPV were surveyed, 57 of them were diagnosed with HBP. The state of the oral cavity was assessed by biochemical parameters of saliva: elastase activity and MDA content (inflammation markers), urease activity (bacteriological contamination marker), lysozyme (nonspecific immunity index), catalase activity (antioxidant enzyme). Mixed oral fluid was collected on the 1st day and on the 14th day after standard treatment according to the protocol. Results: In patients with fractures of the jaw increases the activity of elastase and urease, reduced activity of lysozyme and catalase, especially in patients with HBP. The treatment reduces the activity of elastase and urease and increases the activity of catalase. In patients with HBP standard treatment does not reduce the activity of elastase and urease and does not increase the activity of catalase and lysozyme. The conclusion: HBP complicates inflammation and dysbiosis in the oral cavity in patients with fractures of the jaw, which requires the use of hepatoprotectors.